INTERVIEWING A ROBOT: Notes on the experimental application of the EEAF methodology using the ChatGPT artificial intelligence tool. - dos Santos, Márcio Carneiro (2023)
It presents the methodology EEAF - Exploratory Interview for the Evaluation of Functionalities - to be used by Communication researchers, in the study of characteristics or analysis of textual material, created by artificial intelligence algorithms. In this work we use the ChatGPT conversation tool and propose a set of metrics: transparency, structuring, precision, variety and updating, for evaluation in the experiment. In general, texts created via code showed the need for human review, especially in materials that dealt with objective facts and data.